Targeted protein degradation and the enzymology of degraders. (June 2018) - Fisher, Stewart L; Phillips, Andrew J
Abstract : Targeted protein degradation is an emerging strategy for drug discovery that employs small molecules to catalyze the ubiquitination of target proteins, ultimately causing their degradation by the proteasome. Current degrader designs employ hetero-bivalent molecules to recruit E3 ubiquitin ligases such as VHL, Cereblon, and the IAPs to the target protein to be ubiquitinated. In this review, we describe some of the foundational studies underpinning the use of heterobivalent degraders for targeted protein degradation. We also present a framework for degraders as programmable essential activators of ubiquitin ligase enzymes, connecting their features as catalysts with established enzymology concepts.